Європейське бачення Альтьєро Спінеллі - Морозов, С. О. (Видавництво НДУ ім.М. В. Гоголя, 2017)
Європейський Союз є найбільш успішним і зразковим прикладом регіональної інтеграції. Історія об'єднавчих процесів країн Західної та Центрально-Східної Європи налічує понад шістдесят років. Вони супроводжувалися своїми злетами і падіннями: інтенсивні фази змінювалися відносними спадами активності. Але кожен період по- своєму унікальний і приніс справі об'єднання європейських держав свої особливості та позитивні досягнення. У різний час заради створення ЄС працювали такі видатні особистості як Жан Моне, Робер Шуман, Поль-Анрі Спаак, Жорж Спеналь, Апьтьєро Спінеллі та інші. Паралельно з практичними заходами, спрямованими на об'єднання регіону, розроблялися і теоретичні підвалини європей- ської інтеграції. Одним із тих, хто уособлював обидві сторони діяльності зі створення ЄС, був А. Спінеллі. Пік його політичної активності приходить на один із найскладніших періодів в історії інтеграційних процесів.
The European Union is the most successful and exemplary example of regional integration. The history of the Western and Central-Eastern European countries unification processes is more than sixty years old. They were accompanied by its ups and downs: the intensive phases were replaced by slower activity. But every period is unique and brought some features and positive achievements to the cause of the European states unification. Such famous personalities as Jean Monnet, Robert Schumann, Paul-Henri Spaak, Georges Spenale, Altiero Spinelli and others worked for the EU creation at different times. Practical measures to unite the region were accompanied by the development of the European integration theoretical foundations. One who personified both sides of the EU creation activity was A. Spinelli. The peak of his political activity is one of the most difficult periods in the integration processes history. The paper is devoted to the formation of views, ideas and activities of Altiero Spinelli, the founder of the European integration federalism theory. Mainly, the attention is focused on the practical activities of the famous Italian person, his battle for the united Europe creation and the contribution to the making of the European Union. It is considered more than forty years of European federalist political activity and evaluated his action.
Keywords: Альтьєро Спінеллі; федералізм; політична інтеграція; Altiero Spinelli; federalism; integration, the European Union